Future Emerging Issues in waterborne diseases and microbial agents - Sherchand, JB (Journal of Institute of Medicine Nepal, 2013)
DOI: http://dx.doi.org/10.3126/joim.v34i3.8905 Journal of Institute of Medicine, December, 2012; 34:1-3